Biomass and potential feeding, respiration and growth of zooplankton in the Bransfield Strait (Antarctic Peninsula) during austral summer - Hernandez-Leon, S.; Almeida, C.; Portillo-Hahnefeld, A.; Gomez, M; Montero, I. (0722-4060, 2000)
Biomass (as dry weight and protein content), gut fluorescence, electron transfer system (ETS) and aspartate transcarbamylase (ATC) activities were studied in different size fractions (200–500, 500–1000 μm and 1–14 mm) in the Bransfield Strait (Antarctic Peninsula) during January 1993. Very low values of zooplankton biomass were observed in all the size classes studied. About 56% of total biomass was due to the large size fraction (1–14 mm) while the smallest one (200–500 μm) accounted for about 26%. Gut fluorescence values increased in relation to the size class considered, as expected, being the differences from the smaller to the highest size fractions of orders of magnitude. Calculated ingestion rates showed that about 60–80% of total zooplankton ingestion (<14 mm) was due to the smaller organisms. Higher average values and higher variability of specific ETS activity was observed in the smaller size fraction while no differences between size classes were observed for the specific ATC activity. Biomass, gut fluorescence, ETS and ATC activities were not significantly different between the Bellingshausen and Weddell waters, although higher standard deviation was normally found at the former area. With the restrictions of using the above indices to estimate physiological rates, potential grazing of mesozooplankton (<14 mm) accounted for a rather low portion (<10%) of the primary production. The index of growth showed high values, suggesting no food limitation of mesozooplankton. Therefore, other processes such as predation should account for the very low biomass found and for the fate of a large portion of primary production. 690 679 1,067 Q2 SCIE